The Influence of Reverse Logistics on the Leading Fast Moving Consumer Goods Retailers in South Africa - Mathu, Kenneth (European Journal of Applied Sciences, 2021)
Background Enterprises endeavoured being competitive in their pursuit for customer satisfaction in provision of product/service in the marketplace. The emergence of supply chain management strategy addressed this objective, as it streamlined the coordination of supply and demand sides of business in enterprises. The forward flow of goods from fast moving consumer goods (FMCGs) suppliers to the end-customers led to accumulation of damaged goods being returned back to the suppliers for replacement through the process of reverse logistics. Objectives This study explored the process of reverse logistics on the leading retailers of fast moving consumer goods in South Africa, to establish how the process influenced their business. Method The study pursued qualitative research methodology and constructivism research paradigm and was grounded in the theory of sustainable development and competitive advantage. Non-probability sampling process was used in which 13 participants were interviewed. The interviews were recorded, transcribed, translated, coded and analysed via Atlas ti.8 software to determine the results. Results The outcome of the study indicated that reverse logistics created value for the retailers through replacement of the damaged goods, improved competitiveness and sustainability due to continuous recovery of value, and waste reduction ensured a cleaner environment. Conclusion The recovery of damaged products through the reverse logistics process benefitted enterprises with additional resources as value-added that improved earnings which made them more competitive. As the process was continuous and reduced waste, it ensured the enterprises’ sustainability and spared environmental degradation.